(untitled) (Sociologisk Forskning, 2004)
Like the concepts ”Gemeinschaft” and ”Gesellschaft”, the concepts ”Lebensführung” and ”Lebensstil”belongs to the sociological tradition. However, due to certain problems of translation the two latter concepts has in English language sociology more or less coalesced into one: ”lifestyle”. The article traces the introduction of the concept of ”Lebensstil” in a sociological context back to Simmels Philosophie des Geldes from 1900, and reconstructs Webers use of the concepts ”Lebensführung” and ”Lebensstil” in Die protestantische Ethik und der ’Geist’ des Kapitalismus from 1904-05 and in his later writings. In the final section some suggestions are made concerning possible ways to use the two concepts in a present day sociological context. The underlying hypothesis of the articleis that it might prove to be valuable to uphold a conceptual distinction in Swedish between ”livsföring” and ”livsstil”, instead of under the influence of English language sociology letting the two coalesce into one concept.